Pengaruh Keputusan Investasi, Profitabilitas terhadap Nilai Perusahaan dengan Kebijakan Dividen sebagai Variabel Moderasi pada Perusahaan Manufaktur Periode 2017-2021 - Lista Utami; Risal Rinofah; Alfiatul Maulida (Universitas Batanghari Jambi, 2025)
This research aims to examine the influence of investment decisions, profitability on company value with dividend policy as a moderating variable. The population of this research is industrial companies listed on the Indonesia Stock Exchange for the 2017-2021 period. This research uses quantitative research, with a purposive sampling method. The data used is secondary data obtained from the company's financial reports. The research results show that the investment decision and profitability variables do not have a significant effect on company value and the dividend policy variable is unable to play a role in moderating the investment decision and profitability variables on manufacturing company value during the 2017-2021 period.